(untitled) (Research, Society and Development, 2021)
Homeopathy is a science that seeks to understand the health-disease process, through the perspective of the organism’s balance and imbalance, and to see it as a whole. It has four basic principles, “Cure for similarity”, “Experimenting with medications in healthy individuals”, “Use of dynamized medications” and “Prescription of individual medications”. And even though it is a recognized therapy, many dental professionals are still unaware of this science. Thus, the objective of this work was to carry out a literature review addressing the application of Homeopathy in Dentistry. A narrative literature review was developed with the theme Homeopathy and its applicability in Dentistry, which was based on works from the years 2010 to 2020. A good reducing effect of chronic periodontitis characteristics was found for periodontics, especially when correlated to conventional therapy; in Pediatric Dentistry, studies show the clinical effect, and may even be associated with other practices that focus on the child’s emotional. In the surgical area, some studies have shown the effectiveness of Homeopathic medicines for edema compared to allopathic medicines. Thus, it can be seen that there are already studies that prove the benefits that Homeopathic medicines provide to dental practice, showing them as alternatives to conventional medicine, however, some experimental studies need more phases to prove their effects.